2007
DOI: 10.1088/0953-2048/20/9/s19
|View full text |Cite
|
Sign up to set email alerts
|

Artificial pinning centres in YBCO thin films induced by substrate decoration with gas-phase-prepared Y2O3nanoparticles

Abstract: Y2O3 nanoparticles prepared by an inert gas phase condensation process were used to introduce artificial pinning centres in YBa2Cu3O7−δ thin films. The areal density of the particles was varied between 120 and 4200 particles µm−2 without changing the mean particle diameter of approximately 9 nm. Y2O3 particles were deposited on TiO2 terminated SrTiO3 (100) single-crystal substrates with areal densities up to 1654 particles µm−2 and subsequently covered with YBa2Cu3O7−δ by off-axis pulsed laser deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Similar nanoscale phases embedded in the YBCO matrix can also be obtained using chemical solution deposition. 9 Artificial pinning centres can also be induced via the substrate decoration technique 10 or quasi multilayer deposition. 6,11,12 Recently, we showed that the introduction of Ba 2 YNbO 6 (BYNO) additions into YBCO films grown by pulsed laser deposition (PLD) at a rate of 5 Hz at 770 C resulted in the formation of nanocolumns of $10 nm in diameter aligned with the c-axis of the YBCO.…”
Section: Introductionmentioning
confidence: 99%
“…Similar nanoscale phases embedded in the YBCO matrix can also be obtained using chemical solution deposition. 9 Artificial pinning centres can also be induced via the substrate decoration technique 10 or quasi multilayer deposition. 6,11,12 Recently, we showed that the introduction of Ba 2 YNbO 6 (BYNO) additions into YBCO films grown by pulsed laser deposition (PLD) at a rate of 5 Hz at 770 C resulted in the formation of nanocolumns of $10 nm in diameter aligned with the c-axis of the YBCO.…”
Section: Introductionmentioning
confidence: 99%
“…Several nano-engineering techniques were recently developed to insert and control APCs and, as a consequence of this, the transport performances of YBCO and REBCO films were dramatically enhanced. Many research groups were involved in the challenge of increasing the performance of coated conductors (CC) by APCs, and a lot of papers were published on this topic so far [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several ways of externally inducing normal regions in superconductors have been demonstrated. They include: irradiation by swift heavy ions, artificially introduced regular arrays of holes, artificially introduced nanoparticles that create columnar defects in superconducting films, or surface decoration of the substrate upon which the superconducting film is grown (Civale et al, 1991;Augieri et al, 2010;Mele et al,2006;Sparing et al, 2007). However, classic nonmagnetic pinning becomes ineffective at high temperatures making it difficult to imagine practical applications of HTS materials.…”
Section: The Use Of Afm/mfm Techniques For the Study Of Hybrid Interfmentioning
confidence: 99%